Isotonic NaCl intake by cell-dehydrated rats - Pereira, DTB; Vendramini, Regina Célia [UNESP]; David, R. B.; Nozaki, P. N.; Menani, José Vanderlei [UNESP]; De Luca, L. A. (Elsevier B.V., 2002)
Male adult rats that received an intragastric load of 2 ml of 12% NaCl (n = 13) ingested both water (4.0 +/- 0.2 ml/2 h) and 0.9% NaCl (3.7 +/- 1.0 ml/2 h) when compared with rats that received intragastric load of 2 ml ofwater(water: 0.1 +/- 0.1; 0.9% NaCl: 0.5 +/- 0.3 ml/2 h, n = 12) in a two-bottle test. Intragastric sodium load increased plasma sodium concentration and osmolality by 5% and reduced plasma renin activity by half compared to rats that received intragastric load of water. Intravenous infusion of 1.5 ml/10 min of 10% NaCl (n = 16) also induced ingestion of water (6.2 +/- 0.8 ml/2 h) and 0.9% NaCl (2.9 +/- 0.8 ml/2 h) compared with intravenous infusion of 1.5 ml/10 min of 0.9% NaCl (water: 0.9 +/- 0.4; 0.9% NaCl: 0.5 +/- 0.2 ml/2 h, n = 14). Therefore, a sodium load that raises natremia and plasma osmolality, and therefore induces cell dehydration, results in both 0.9% NaCl and water ingestion when the rats have a two-bottle choice. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: thirst; dehydration; renin; sodium intake; hypertonicity; hyperosmolarity